Comparable analysis of bubble translation due to acoustic radiation force based on simultaneous acoustical and optical observation. (15th April 2020) - Yoshida, Kenji; Saito, Katsuya; Omura, Masaaki; Yamaguchi, Tadashi
Abstract: Contrast-enhanced ultrasound imaging using acoustic radiation force, called contrast-enhanced active Doppler ultrasound (CEADUS) imaging, has been proposed for visualizing lymph channels filled with stationary fluid. Based on optical observations and acoustical evaluation, the behaviour of bubbles in a simulated channel during ultrasound exposure was investigated under four conditions for negative peak sound pressure ( P np ), at centre frequency of ultrasound and pulse repetition frequency of 15 MHz and 1 kHz, respectively. There was good correlation between the time changes of mean translational velocity for optical evaluation ( V OPT ) and acoustical evaluation ( V US ). In addition, the maxima of V OPT and V US were correlated ( R  = 0.665) and showed a similar trend proportional to the square of P np . These results strongly suggest that the acoustically-evaluated bubble translation has information equal to optically-evaluated one, meaning that the simultaneous observation system is useful to understand the bubble behaviours under CEADUS imaging.